Effects of Lactobacillus fermentum GKF3 on Reducing Smoking and Brain Neurotransmitter Levels: Findings From Animal and Human Studies - You‐Shan Tsai; Shan Lin; Chin‐Chu Chen; Chun‐Hung Chiu; Mei‐Chin Mong; Shu‐Ling Hu; Chi‐Hao Wu (Food Frontiers)
ABSTRACT The efficacy of smoking cessation therapies primarily relies on modulating brain dopamine levels. Given the ability of psychobiotics to modulate neurotransmitter release via the gut‐brain axis, this study investigated the potential of Lactobacillus fermentum GKF3 supplementation to reduce smoking in adults. A preliminary physical restraint study in ICR mice demonstrated that 4 weeks of GKF3 gavage significantly elevated brain dopamine and serotonin levels, suggesting potential efficacy in smoking reduction. Subsequently, a randomized, single‐blind, crossover study was conducted with 45 habitual smokers. Each participant provided informed consent and received either a placebo or GKF3 capsule (2.0 × 1010 colony‐forming units [CFU]/day) for 4 weeks, followed by a 2‐week washout period and crossover to the alternate treatment arm for an additional 4 weeks. The primary outcome was daily tobacco exposure, estimated by measuring nicotine and its metabolites (cotinine and trans‐3′‐hydroxycotinine) in urine using LC–MS/MS. Results showed that the GKF3 group had a significantly greater reduction rate (67%, 30/45) in nicotine and its metabolite levels compared to the placebo group (36%, 16/45, p = 0.0031). No significant differences were observed between groups in oxidative stress parameters before or after the intervention (p > 0.05). In conclusion, supplementation with L. fermentum GKF3 effectively reduces smoking, potentially through the modulation of monoamine neurotransmitters in the brain. This study provides initial evidence supporting the use of probiotics as a complementary therapy for smoking cessation.